Hirsch o interpretacji. Analiza krytyczna - Szahaj, Andrzej (Przestrzenie Teorii, 2013)
The main aim of the article is to reconstruct and critique E.D. Hirsch’s position in the debate about the necessary conditions and results of any interpretation. The author of this article seeks to demonstrate the difficulties connected with the intentionalist approach to the theory of interpretation which is typical of E.D. Hirsch and which unjustifiably privileges authorial intention. He also attempts to uncover the hidden assumptions of this approach by showing that, generally speaking, the dualist tendencies that are present in Hirsch’s theory cannot be justified. One of the objectives of this article is to propose an alternative approach to interpretation, which has been inspired by Stanley Fish and which emphasizes the integrity and monistic nature of interpretation as well as its constructivist and inevitably evaluative character. The author points to the fact that the arbitrarily established evaluation limits are unjustified as there is an element of evaluation on every level of interpretation and that the difference between understanding and interpretation cannot be validated. Also, one cannot interpret a text without each time referring to the social and cultural context.